4. Identification Endoparasites Of Wildboar (Sus scrofa) In Lhoknga Aceh Besar - Azhar Azhar; Boni Cutami Rusty; Muttaqin Bakri; Farida Farida; Nazaruddin Nazaruddin4; Zuhrawaty Zuhrawaty (Universitas Syiah Kuala, 2020)
This research was aimed at the identification of endoparasites in wild boar (Sus scrofa) in the district area Lhoknga Aceh Besar. Many six wild boars were used in this research and examined at the laboratory Parasitology in the Veterinary Medicine faculty at Universitas Syiah Kuala. The wild boar was trapped and using cough at the traditional tool. The identification of endoparasites was done by direct examination. The result of observation on the feces was obtained endoparasites Ascaris suum with a prevalence of 50% and Oesophagostomum dentatum with a prevalence of 15%. Based on these results it can be concluded that the infestation of endoparasites in wild boars feces (Sus scrofa) were Ascaris suum and Oesophagostomum dentatum.